The prevalence of anemia in patients with malignant tumors: a hospital based cross sectional study - Dafalla O. Abuidris; Omer Abdelbagi; Reem Altayeb; Hiba Elrashid Yagoub; Osama Al-Wutayd; Ishag Adam; Mohammed Alorini (Italian Journal of Medicine, 2023)
Cancer is a worldwide health problem, and anemia is one of its manifestations. There are no published data on anemia among patients with cancer in Sudan. The current study aimed to investigate the prevalence of anemia among patients with malignant tumors in central Sudan. The medical records of patients with malignant tumors admitted to the National Cancer Institute, University of Gezira, Sudan, from March to December 2020 were reviewed. Among the 471 patients enrolled in the study, 292 (62.0%) were female. The median (interquartile range, IQR) age was 55 (45-66) years. Breast cancer (109, 23.1%), colorectal/anorectal (88, 18.7%), head and neck (83, 17.6%), female genital tract (70, 14.9%), and prostate (35, 7.4%) cancer were the main cancers observed in this study. The median (IQR) hemoglobin was 11.9 (10.5-13.0) g/dl and 237 (50.3%) patients had anemia. The prevalence of anemia ranged from 31.2% in breast cancer patients to 82.9% in those with prostate cancer. Compared with males (120/292, 41.1%), females (117/179, 65.4%) had a significantly higher prevalence of anemia (P<0.001). The median (IQR) age of the patients with anemia was significantly higher than that of those without anemia (57.0 years vs. 51.5 years, respectively; P=0.003). Half the patients with malignant tumors had anemia. Anemia was more common among female patients and elderly patients.